Anomalous Deposition of Co-Ni Alloys in Film and Nanowire Morphologies from Citrate Baths. (1st December 2016) - Dryden, Daniel M.; Sun, Theodore; McCormick, Ryan; Hickey, Raymond; Vidu, Ruxandra; Stroeve, Pieter
Abstract: Thin films and nanowires were deposited across the full range of Co-Ni solution compositions via templated electrodeposition in citrate baths. Spectroscopic analysis indicated a high degree of anomalous deposition across all alloy compositions, with no significant composition differences seen between films and nanowires. Electrochemical and microstructural analyses indicated notable differences between structures deposited in low- and high-Ni environments.